PENINGKATAN KEMAMPUAN MENULIS LAPORAN ILMIAH SEDERHANA BERDASARKAN STRATEGI PEMODELAN BAGI SISWA KELAS VIII A SMP NEGERI 20 PALU - Abas, Kusnadiyanto; Tahir, Moh.; Karim, Ali (BAHASANTODEA, 2018)
This research aims to: (1) improve writing simple scientific report ability through modeling strategy for the students of class VIII A at SMP Negeri 20 Palu Central Sulawesi and (2) describe the improvement of writing simple scientific report ability based on modeling strategy. This research was a classroom action research conducted in two cycles. The subjects of this research were 20 students of class VIII A at SMP Negeri 20 Palu. Procedures for implementing a classroom action research: (1) action planning, (2) action implementation, (3) observation, and (4) reflection. Based on the results of the research on improving writing simple scientific report ability through modeling strategy, it is concluded that there is a significant improvement. The result of the research on pre-action is 58 with the percentage of 18% classical learning achievement. Next, an action is implemented in cycle I with the average score is 71.5 with 50% classical learning achievement percentage. Then proceed to cycle II with the average value of 84.42 and the percentage of 92.85. Based on the result, it can be concluded that using modeling strategy can improve the ability of students in class VIII A at SMP Negeri 20 Palu in writing simple scientific report. Improving students' ability to write simple scientific reports through modeling strategy deserves to be considered as a classroom action material for teachers and subsequent researchers. The final result of this research shows that the application of modeling strategy in learning to write simple scientific report can improve students’ competence. Aspects assessed include; systematic of writing, grammar, effective sentences and neatness of writing.